Legal Basis of the Treasury System in Local Governments in the Second Republic of Poland - Anna Tarnowska (Prawo Budżetowe Państwa i Samorządu)
The author of the article presents the legal basis of the treasury system of the local government during the period of so called Second Republic of Poland (1918–1939) i.e. “interwar period”. The author indicates a discrepancy between systems of the former Russian, Prussian and Austrian districts, aside from the autonomous Silesian Voivodeship created in 1920, and numerous issues distinctive for process of unification, not actually successful solved until 1939. The basic provisions were provided for in Provisional settlement of communal finances Act from 1923, amended several times and officially valid until the post-war years. The matter of local budgets has been standardized in the President`s Decree from 1924 concerning obligations and procedure of covering expenditures of local governments. Nevertheless, given regulations constituted a complicated, overextended and casual system.